2013
DOI: 10.1073/pnas.1313575110
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of TLR adapter TRIF to TLR4 signaling complex is mediated by the second helical region of TRIF TIR domain

Abstract: Toll/IL-1R resistance (TIR) domain-containing adapter-inducing IFN-β (TRIF) is a Toll-like receptor (TLR) adapter that mediates MyD88-independent induction of type I interferons through activation of IFN regulatory factor 3 and NFκB. We have examined peptides derived from the TRIF TIR domain for ability to inhibit TLR4. In addition to a previously identified BB loop peptide (TF4), a peptide derived from putative helix B of TRIF TIR (TF5) strongly inhibits LPS-induced cytokine and MAPK activation in wild-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 40 publications
4
69
0
Order By: Relevance
“…Furthermore, these studies provided novel insights into the structural interactions and function of TIR domains that could potentially augment the efficacy of TLR agonists and antagonists. Fekonja et al (2012b) showed that the addition of a strong-coiled coil dimerization domain determined the degree of inhibition against various TLRs and prevented activation of the dimeric TIR platform and Piao et al (2013a) identified TRIF sites that are important for interaction with TLR4 and TRAM. Intense interest in the BB loop of TIR domain has guided research efforts in the development of inhibitory peptides (Toshchakov et al, 2007(Toshchakov et al, , 2011Piao et al, 2013a).…”
Section: Novel Approaches For Targeting Toll-like Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these studies provided novel insights into the structural interactions and function of TIR domains that could potentially augment the efficacy of TLR agonists and antagonists. Fekonja et al (2012b) showed that the addition of a strong-coiled coil dimerization domain determined the degree of inhibition against various TLRs and prevented activation of the dimeric TIR platform and Piao et al (2013a) identified TRIF sites that are important for interaction with TLR4 and TRAM. Intense interest in the BB loop of TIR domain has guided research efforts in the development of inhibitory peptides (Toshchakov et al, 2007(Toshchakov et al, , 2011Piao et al, 2013a).…”
Section: Novel Approaches For Targeting Toll-like Receptor Signalingmentioning
confidence: 99%
“…Fekonja et al (2012b) showed that the addition of a strong-coiled coil dimerization domain determined the degree of inhibition against various TLRs and prevented activation of the dimeric TIR platform and Piao et al (2013a) identified TRIF sites that are important for interaction with TLR4 and TRAM. Intense interest in the BB loop of TIR domain has guided research efforts in the development of inhibitory peptides (Toshchakov et al, 2007(Toshchakov et al, , 2011Piao et al, 2013a). The BB loop peptides, however, lack specificity for a specific TLR or TLR-adapter complex because they bind to proteins containing TIR domains with variable affinity (Toshchakov et al, 2007(Toshchakov et al, , 2011Fekonja et al, 2012a;Piao et al, 2013a).…”
Section: Novel Approaches For Targeting Toll-like Receptor Signalingmentioning
confidence: 99%
“…The intracellular region of TLR4 also contains clusters of missense mutations within the Toll/IL-1 receptor (TIR) domain (Fig. 1A), which are essential for the recruitment of intracellular effectors of TLR4 signaling, including myeloid differentiation primary response 88 and TIR domain-containing adaptor protein (2,3). This mutational profile suggests that TLR4 gene function is disrupted in some breast tumors in which TLR4 may function as a tumor suppressor gene.…”
Section: Tlr4 Is Frequently Mutated In Er-positive High Mutation Loadmentioning
confidence: 99%
“…TLR4 is activated by a variety of ligands: DNA, RNA, and viral particles; chemotherapeutic agents; and lipopolysaccharides (LPS). TLR4 induction in immune cells can activate numerous cancer-associated signaling cascades, including the MAP kinase and NFkB pathways (2,3). These pathways transcriptionally activate the secretion of either proinflammatory cytokines, such as IL-6 and IL-8, or anti-inflammatory type I IFNs, including IFN-γ.…”
mentioning
confidence: 99%
“…For antagonist inhibition assay, zebrafish were pretreated 1 h via i.p. with two TRIF antagonist peptides (with a penetration sequence at the N terminus) derived from a mice model (41,42). The sequences of the peptides for DrTRIF (DrT1 and DrT2) and control are shown as follows: RQIKIWFQNRRMKWKK-CIEDAI DNSAFV-NH2 (DrT1), RQIKIWFQNRRMKWKK-FSEDFAQAGRSTLR-NH2 (DrT2), and RQIKIWFQNRRMKWKK-SLHGRGDPMEAFII-NH2 (DrControl).…”
Section: Evaluation Of Drsigirr and Drtrif In Liver Inflammationmentioning
confidence: 99%